Strategi Organisasi Al Jam’iyatul Washliyah dalam Syiar Dakwah Melalui Media Sosial di Kota Medan - Muhaammad Andi Harahap; Salamuddin Salamuddin (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The development of da'wah broadcasting in Indonesia is marked by the rise of social media users in various cities, such as social media belonging to the Al Jam'iyatul Washliyah Organization which is one of the strategies for spreading da'wah with the aim of practicing Islamic teachings for the sake of happiness in this world and the hereafter. The Al Jam'iyatul Washliyah organization, better known as Al Washliyah, is an Islamic organization that successfully carries out its missionary activities through mosques, education and also social media. In this research, the researcher raised a special topic regarding the concept of spreading da'wah through social media YouTube, Facebook, Instagram. A qualitative research method was chosen for this research with a descriptive case study approach. Primary data collection techniques were carried out using interviews and direct observation, while secondary data was obtained through literature studies carried out on various reading sources that were relevant to the research topic. The research results show that social media carried out by the Al Jam'iyatul Washliyah organization among the public can make it easier for the younger generation to access information about Islamic da'wah and can also change attitudes to always listen to Islamic da'wah.